ANALYSIS OF SCHOOL READINESS IN IMPLEMENTING DIGITAL LEARNING: CASE STUDY IN CIPUTAT, SOUTH TANGERANG - Kultsum, Ummi (BAIK Publishers, 2025)
Digital transformation in education requires the readiness of school institutions in various aspects, from infrastructure to curriculum adaptation. This study aims to analyze school readiness in implementing digital learning in the Ciputat area, South Tangerang. The study used a qualitative approach with a case study method in three schools with different characteristics. Data collection techniques included in-depth interviews, observations, and documentation studies. The results of the study showed that school readiness still varies greatly. Schools with adequate managerial and financial support tend to be more prepared, as indicated by the availability of digital infrastructure, good teacher competence, and a curriculum that has adapted to digital learning. Meanwhile, limited facilities, low digital literacy of teachers and students, and minimal training are the main obstacles for other schools. In conclusion, the successful implementation of digital learning requires synergy between technical readiness, human resources, and curriculum policies. This study provides implications for education policy makers in designing strategies for equalizing digital transformation in schools